2009
DOI: 10.1177/1941406409355192
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Knowledge and Confidence Levels of Parents of Children With Cystic Fibrosis

Abstract: Optimal growth and nutrition status predict better lung function and longevity for children with cystic fibrosis (CF). Daily nutrition therapy for children with CF requires adequate food resources, parental knowledge of nutrition and behavior management, and confidence in one’s ability to apply the skills. The Mountain West Cystic Fibrosis Consortium Questionnaire (MWCFC-Q) was designed to identify educational intervention targets to improve the growth and nutrition of children with CF. Parents of children wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 15 publications
1
16
1
Order By: Relevance
“…McDonald et al did a cross-sectional study on nutritional knowledge and confidence levels of parents of children with CF. They found that confidence scores were lower for nutritional aspects of care as compared to pulmonary aspects of care [29]. There are numerous new skills parents and caregivers need to learn and having the confidence in difficult situations is not innate-it is developed and shaped by a variety of factors [30].…”
Section: Predictors Of Overall Experience With the Health Care Teammentioning
confidence: 99%
See 2 more Smart Citations
“…McDonald et al did a cross-sectional study on nutritional knowledge and confidence levels of parents of children with CF. They found that confidence scores were lower for nutritional aspects of care as compared to pulmonary aspects of care [29]. There are numerous new skills parents and caregivers need to learn and having the confidence in difficult situations is not innate-it is developed and shaped by a variety of factors [30].…”
Section: Predictors Of Overall Experience With the Health Care Teammentioning
confidence: 99%
“…Ways to improve confidence include planning, preparing and learning [30]. Growth and development early in life are critical to the course of CF and building a parent's confidence may be one of the many factors needed [29]. Behavioral interventions and nutritional education have been shown to improve nutritional status in children with CF [31][32][33][34] and may in part relate to building confidence of the parents.…”
Section: Predictors Of Overall Experience With the Health Care Teammentioning
confidence: 99%
See 1 more Smart Citation
“…The nutritional status of children with CF relies on parents' abilities to effectively manage dietary and behavioral issues [5]. Previous research at this center suggested opportunities for improvement in parents' knowledge and confidence in their ability to manage nutrition concerns for their children with CF [6]. Parents reported more confidence in their abilities to manage tasks such as respiratory therapy, oral and inhaled medications, and minor illnesses at home than nutrition-related CF issues [6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research at this center suggested opportunities for improvement in parents' knowledge and confidence in their ability to manage nutrition concerns for their children with CF [6]. Parents reported more confidence in their abilities to manage tasks such as respiratory therapy, oral and inhaled medications, and minor illnesses at home than nutrition-related CF issues [6]. Interviews with families suggested a perception that tasks tend to be more concrete and less emotional than management of nutrition-related issues such as weight gain, differing dietary recommendations for various family members, and behavioral issues around eating [6].…”
Section: Introductionmentioning
confidence: 99%